Simple and subdirectly irreducibles bounded distributive lattices with unary operators - Sergio Arturo Celani (International Journal of Mathematics and Mathematical Sciences)
We characterize the simple and subdirectly irreducible distributive algebras in some varieties of distributive lattices with unary operators, including topological and monadic positive modal algebras. Finally, for some varieties of Heyting algebras with operators we apply these results to determine the simple and subdirectly irreducible algebras.